Effects of Temperature and Salinity on Egg Production, Hatching, and Mortality Rates in Acartia ohtsukai (Copepoda, Calanoida) - Choi, Seo Yeol; Lee, Eun Hye; Soh, Ho Young; Jang, Min-Chul (Frontiers in Marine Science, 2021)
The calanoid copepod Acartia ohtsukai predominates the estuarine and coastal waters of East Asia during summer. Its occurrence characteristics confer it with good potential as live prey for fish larvae through mass culture. To investigate the effect of temperature and salinity combinations on its egg production (EPR), hatching success (HS), and mortality rate, experiments were undertaken and repeated three times for combinations of five temperatures (10, 15, 20, 25, and 30℃) and seven salinities (10, 15, 20, 25, 27, 30, and 33 psu). EPR and HS were highest at temperatures of 25℃ and 30℃, respectively, with a salinity of 27 psu. Mortality rate was highest at 10℃ in almost all salinity gradients, whereas it was lower at water temperature and salinity ranges of 20–30℃ and 20–30 psu, respectively. These findings indicate that A. ohtsukai can inhabit wide ranges of water temperatures and salinities, and that the optimized condition for mass culture is a combination of water temperature of 25℃ and salinity of 27 psu.